Representasi Stereotype Perempuan Dalam Film Kartini (2017) - Amelia Rosyadi; Yustafad (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This research was conducted to fight for gender equality to explore the ability of stereotypical representations of women shown in the film Kartini (2017). This movie is a biographical documentary made by Legacy Pictures. There are criticisms that this film raises stereotypes of women behind Kartini's personality who dares to fight against the culture that has existed for generations. This type of research is qualitative with Content analysis method. The theory used is gender theory including Nurture Theory, Equilibrium Theory. Meanwhile, the object of research to be analyzed is the representation of female stereotypes. Indeed, in the beginning, the movie Kartini (2017) tried to break the stereotypes of women who have always been a hereditary culture, namely only as servants. The objectives of this study include first, describing Kartini's role in the struggle for gender equality. Second, to investigate the impact of family and culture on gender roles. Third, review Kartini's efforts to improve women's education and economy. The results show the efforts of the movie Kartini (2017) in breaking generational stereotypes about women, especially those that show women only as servants, receiving messages of women's empowerment and gender equality. And here reveals the concept of Women Empowerment (Women's Empowerment rights regardless of gender).